The Effect of Value Co-Creation, and Corporate Image on Building Customer Loyalty Toward Apartment Contractor - Setijanto, Augustinus; Hardjomuljadi, Sarwono; Waty, Mega (LPPM of NAROTAMA UNIVERSITY, 2024)
The purpose of this study is to create strategy for apartment contractors to build loyalty of apartment developer by examine customer satisfaction as mediator between corporate image, vccreation with customer loyalty in the Indonesia apartment construction industry. Current study is conducted in the apartment construction industry in Indonesia. The population for this study is apartments developer in Indonesia. To accomplish main purpose, the data were collected from project managers of apartment developer firms in Indonesia. Online questionnaires were distributed and total of 316 respondents’ data were collected and analysed. Respondent data was processed using SmartPLS for hypothesis testing. The results shows that customer loyalty significantly influenced by their satisfaction, corporate image, and vccreation. The result also reveals that customer satisfaction mediate the relationship between corporate image, vccreation and with customer loyalty. Furthermore, the research results also found that corporate image, vccreation and positively influence satisfaction.